What should be done about rising unemployment in the UK? - Bell, David N.F.; Blanchflower, David G. (Bonn, 2009)
"This paper considers the issue of unemployment one of the most pressing issues facing the UK and other governments, as the current recessions deepens. It begins by trying to accurately date the beginning of the current downturn in the British economy, arguing that it is clear that the recession commenced in the 2nd quarter of 2008. It then examines whether this recession is substantively different from past downturns in the UK and argues that, although the extreme rationing up of credit marks the current recession as different, some of the labour market consequences, such as the concentration of unemployment among the young and other disadvantaged groups, is typical of past experience. The paper reviews past literature on the causes of unemployment, arguing that the origin of the present difficulties lies with a collapse in demand rather than with frictions in the labour market caused by institutional inflexibilities. There is a large literature on the negative impact of unemployment both on society and on individuals. The adverse societal consequences are reviewed in the next section, while we discuss some of our own research on the adverse consequences on the individual in Section 6. Just as in previous recessions, it is becoming clear that some groups will suffer a much higher incidence of unemployment during this downturn and therefore suffer to a greater than average extent the adverse individual effects that we discussed in Section 6. The evidence on the composition of these groups is reviewed and presented along with some of our own research on this issue in the following section. One of the key groups who are likely to be affected by the recession is the young. In Section 8, we review the particular difficulties faced by them in trying to secure a footing in the labour market. In the last two decades many governments have introduced policies (collectively described as Active Labour Market Policies or ALMPs) for direct intervention in the labour market to improve outcomes for particular groups and for the young in particular. The next section reviews the evidence on the success of these policies. The final section discusses some policy proposals which we offer to alleviate what we believe will be the very serious adverse consequences of the likely increase in unemployment in the UK over the short to medium term."